Taxonomic review of the millipede genus Haematotropis Jeekel, 2000 (Diplopoda, Polydesmida, Aphelidesmidae, Aphelidesminae) with descriptions of thirteen new species - Almeida, Thaís M. de; Bueno Villegas, Julián; Rafael, José Albertino (Zootaxa, 2021)
The northern South American genus Haematotropis Jeekel, 2000 is shown to presently encompass 21 species, all duly redescribed, illustrated, keyed, and mapped, including 13 new species: H. amazonica sp. nov. (Amazonas, Brazil), H. aripuanensis sp. nov. (Mato Grosso, Brazil), H. callyi sp. nov. (French Guiana), H. dentata sp. nov. (Maranho, Brazil), H. disjunctoides sp. nov. (Par, Brazil), H. goeldii sp. nov. (Par, Brazil), H. jurutiensis sp. nov. (Par, Brazil), H. driki sp. nov. (Amazonas, Brazil), H. melgacensis sp. nov. (Par, Brazil), H. mosaica sp. nov. (Par, Brazil), H. paraensis sp. nov. (Par, Brazil), H. poranga sp. nov. (Par, Brazil) and H. tysoni sp. nov. (Amazonas, Brazil). New characters are used in all descriptions and redescriptions. Aphelidesmus guianensis Chamberlin, 1923, the type species of Ochrotropis Jeekel, 2000, is a new junior synonym of Aphelidesmus divergens Chamberlin, 1918, comb. nov. ex Ochrotropis in Haematotropis
Keywords: Diplopoda; Polydesmida